Performance, trauma and Puerto Rico in musical theatre - Rua, Colleen (Routledge advances in theatre & performance studies, 2023)
"This study positions four musicals and their associated artists as mobilizers of defiant joy in relation to trauma and healing in Puerto Rico. The book argues that the historical trajectory of these musicals has formed a canon of works that have reiterated, resisted or transformed experiences of trauma through linguistic, ritual, and geographic interventions. These traumas may be disaster-related, migrant-related, colonial or patriarchal. Bilingualism and translation, ritual action, and geographic space engage moments of trauma (natural disaster, incarceration, death) and healing (community celebration, grieving, emancipation) in these works. The musicals considered are West Side Story (1957, 2009, 2019); The Capeman (1998); In the Heights (2008); and Hamilton (2015). Central to this argument is that each of the musicals discussed is tied to Puerto Rico, either through the representation of Puerto Rican characters and stories, or through the Puerto Rican positionality of its creators. The author moves beyond the musicals to consider Lin-Manuel Miranda as an embodied site of healing, that has been met with controversy, as well as posthurricane Maria relief efforts led by Miranda on the island and from a distance. In each of the works discussed, acts of belonging shape notions of survivorship and witness. This book also opens a dialogue between these musicals and the work of island-based artists Y no haba̕ luz, that has served as sites of first response to disaster. This book will be of interest to students and scholars in Latinx Theatre, Musical Theatre and Translation studies"--